Small-Data Computing: Correct Calculator Arithmetic. - BOEHM, HANS-J. (Communications of the ACM, 2017)
The article discusses the processes and methodologies used in calculator arithmetic as well as the small-data computing necessary for such mathematics in smartphone calculators. It details how computers perform numerical computations using floating point arithmetic before describing efforts to replace arithmetic evaluation engines used in Android operating system calculators with one not subject to floating point-rounding errors.